The Effectiveness of Badminton-Based Physical Education Learning Modification on Improving Students' Motor Skills - Ishak, Muhammad; Sahabuddin, Sahabuddin; Hasanuddin, M. Imran (JOURNAL RESPECS (Research Physical Education and Sports), 2025)
This study investigates the effectiveness of a modified badminton-based physical education learning model in improving students' motor skills at SMA Negeri 16 Makassar. Using a quasi-experimental design with pretest-posttest control group, 60 students were divided into experimental and control groups. The experimental group received the modified badminton-based PE intervention for 8 weeks, while the control group followed the standard PE curriculum. Motor skills were assessed using validated instruments from TGMD-3 and MABC-2, including agility (shuttle run), balance (stork stand), coordination (wall toss), reaction time (ruler drop), and speed (30-meter sprint). Posttest results indicated statistically significant improvements in all motor skill domains for the experimental group: agility improved by 19.6%, balance by 21.3%, coordination by 17.4%, reaction time by 15.7%, and speed by 12.8% (p < 0.05). In contrast, the control group showed minimal changes. These findings suggest that badminton-based physical education is highly effective in enhancing students’ motor competencies. The study recommends integrating modified sport-specific models into PE curricula to promote motor skill development and physical literacy.